Linguistic Landscape Analysis of Identity Representation in Public Signs at Watugong Buddhist Monastery Semarang - Lery Prasetyo; Ketut Artawa; Ketut Widya Purnawati3; I Wayan Suardiana (Randwick International of Education and Linguistics Science Journal, 2024)
Public signs at Watugong Monastery in Semarang serve not only as guides for visitors but also as representations of identity, meaning, and values. This study aims to uncover the meaning and representation of identity in the public signs of Watugong Monastery by considering the cultural, religious, and social contexts in accordance with the dominant ideology in the place. This study uses a qualitative descriptive method with a Barthes (1991) semiotics approach. Research data was collected through observation and documentation methods using photography techniques. The results of this study show that there are representations of cultural, religious, and socio-religious identities in the Public signs of Watugong Monastery. Religious identity comes from the interpretation of the object label signs 福 (fú), 祿 (lù), and 壽 (shòu) which reflect Chinese cultural values. Religious identity emerges from hiolo stick sign, which contains the meaning of strong faith in Buddha and his teachings through prayer and devotion supported by morality and exemplary behavior. Finally, socio-religious identity appears on the Ashoka inscription sign, the strong religious element derived from Buddhist teachings, the inscription also shows an example of social life between people of different faiths who must always teach tolerance and moderation in religion. This research is still very open for further research in various other aspects of LL, for example, visitors' perceptions of the language used at Watugong Monastery.